Chiral induction in a novel self-assembled supramolecular system composed of α-cyclodextrin porous liquids, chiral silver nanoparticles and planar conjugated molecules. Issue 5 (11th January 2022) - Wang, Yan; Feng, Zhen; Sun, Yawei; Zhu, Lijun; Xia, Daohong
Abstract : A supramolecular system based on host–guest recognition and electrostatic interaction has been developed for a chiral transfer from α -cyclodextrin porous liquid to planar molecules via the bridge of azobenzene modified silver nanoparticles. Abstract : The newly developed porous liquids known as liquids with permanent microporosity, have considerable application potential in many unknown areas. Herein, a supramolecular system composed of α-cyclodextrin porous liquid, chiral silver nanoparticles and planar conjugated molecules (methylene blue and indigo carmine) was designed and the induced chirality of the system was observed. It was found that the induced chirality can be easily tuned by changing the pH value of the mixture solution. The induced chiral signal of methylene blue in the developed self-assembled supramolecular system occurred when the pH was between 8 and 10, and furthermore the induced chirality of indigo carmine was found when the pH was between 6.5 and 7.5. The intensity of induced chirality decreases upon increasing temperatures and ionic strength. This study may offer a new approach for the creation of a chiral supramolecular system based on host–guest and electrostatic interaction and make cyclodextrin porous liquids promising candidates for applications in chiral induction.